The amendment to the Act of 1964: reconciling the irreconcilability - Mohd Zin, Najibah; Abdul Hak, Nora; Hamid, Abdul Ghafur@Khin Maung Sein; Mohamed Jani, Hidayati (2018)
This paper examines the ramifications of the recent amendment to the Law Reform (Marriage and Divorce) Act 1976 (‘The Act of 164’) in protecting the well-being of the family relationship involving interfaith marriage and other legal issues governing non-Muslim families. The amendment witnessed substantial reforms to section 51 of the Act pertaining to the divorce on the ground of conversion, increasing the age limit for child maintenance and adopting more flexible principles in dividing matrimonial assets. However, the focus will be on the impact of the amendment to section 51 of Act of 164 due to its significant in changing the landscape of legal arguments pertaining to jurisdiction of the court in dealing with the subject matter in dispute, ranging from the divorce and other intense arguments pertaining to maintenance of wife, child custody and religious status of children. The study adopts qualitative study in elucidating relevant documents that comprised of statutory laws, articles in legal journals and decided cases where arguments leading to the need for the reform of those affected issues were well addressed. Certain aspects of Islamic jurisprudence will be referred to and analysed in searching for authoritative and practical legal arguments within the existing legal framework. Harmonisation of law is adopted whenever applicable when dealing with resolution of conflict of laws. It is hope that this study will provide constructive argument and invaluable source of reference for the Malaysian civil court in disposing interfaith family disputes when the law is fully enforced.